DOES FINANCIAL PERFORMANCE AND OPERATIONAL EFFICIENCY INFLUENCED BY ARTIFICIAL INTELLIGENCE DISCLOSURE? - Ade Sri Ulita Br Sembiring; Cristian Abimanyu; Rizkian Saing Marwianto (AIBPM Publisher, 2026)
This study was conducted with the aim of analyzing the influence of Artificial Intelligence (AI) on the Financial Performance and Operational Efficiency of companies. The research method used was a Systematic Literature Review (SLR) of 50 articles published in the journal SINTA 1-6. Of the 50 articles identified and selected in the publication period of 2021-2026 from Sinta 1-6, resulting in 2 (two) articles selected according to the criteria, namely 1 (one) article from Sinta 3, and 1 (one) article sourced from Sinta 5 with a trend of 100% of articles published in 2026. The results of the study from both articles indicate that there is an influence of Artificial Intelligence with a positive correlation on Financial Performance and Artificial Intelligence has no effect and a negative correlation on Financial Performance. Meanwhile, 2 (two) articles that meet the criteria for Artificial Intelligence and the company's Operational Efficiency, namely 2 (two) articles from Sinta 3, show that Artificial Intelligence has an influence and is able to have an impact on the company's operational efficiency. With the proper use of Artificial Intelligence, it can have an impact on the efficiency and accuracy of the company's annual report.Keywords: Artificial Intelligence; Financial Performance; Profitability; ROA; ROE; Operational Efficiency